(untitled) (Archives of Criminology, 2004)
The article presents results of a research conducted for the Ministry of National Education and Sports, which primarily aimed to look closer at the changes in forms, scale and increase of aggressive behaviours of students at all the different learning and upbringing stages. The first kind of such research in Poland was initiated by K. Ostrowska and A. Siemaszko in 1981. Its results were widely discussed by A. Siemaszko in his book „Deviated teenage behaviours”. Next research, which is a direct source of reference for the research discussed in this article, was a countrywide research into aggressive behaviours of students, conducted in 1997 also from the initiative of K. Ostrowska, with a cooperation and extensive financial involvement of prof. Hans Ludwig Schmidt, dr. Janusz Surzykiewicz and the Bosch Foundation. Similarly as in the past, the results were thoroughly presented in a monography „Aggression and School Violence. Socio-economic conditions” written by Janusz Surzykiewicz. The presented research concerning aggressive behaviours of students in 2003, is based on answers of respondents about causing and experiencing aggression across a 12 months period before conducting the research. Questionnaires in self-report technique were conducted in November and December 2003. A group of 16 students was randomly sampled from ministerial lists of primary, lower secondary, general secondary schools, specialised secondary schools, technical secondary schools as well as basic vocational schools. Research has been conducted in all 16 provinces of Poland. In the randomly sampled schools a suitable number of students was randomly sampled from each teaching level. In relation to 1997 the number of surveyed students is smaller, the previous counted 2567 individuals. Contraction of this group was dictated by financial and time limitations of the research. This article includes characteristics of student respondents by their age, kind of school, class, place of living, family situation including family structure, marital status of parents, current residing or other persons, with parents, age of parents, their education and professional activity. The socio-demographic characteristic of the families indicated that in 90% of cases students come from complete families, they have parents, in the age of professional activity (35-50 years of age) with vocational, secondary and higher education. However, there is a worrying fact that about 20% of families is struggling economically due to the lack of permanent employment. The characteristic of aggressive student behaviour concerns, on the one hand, a number and percentage frequency structure of 41 behaviours considered in the research as an indicator of aggression, on the other hand - an analysis according to the differentiated categories of aggression. These are behaviours which have a smaller potential effect – they would cause a considerably smaller, danger, pain, harm, suffering i.e. spreading lies about other students; and ones which could be called examples of serious aggression or even as bearing characteristics of criminal offences such as: threatening with a knife, a razor blade, gas or using a sharp object while in a fight. The most common signs of aggression on the school area the less potentially harmful behaviours, they create a specific school atmosphere. Amongst those to mention would be: cheating on teachers, disrupting teaching in class, offensive talking, calling other students names, writing on school walls and desks, purposeful pushing others, spreading lies and harming oneself by drunkenness. Such forms of behaviour happen to 30 - 40% of respondents. However, as it has been mentioned in detailed descriptions, school is also a place where more serious forms of aggression take prace. These are: forcing students to do things against their will, fighting with other colleagues, group beating of a single student, forcing or provoking sexual behaviouts, using sharp objects in a fight. The article incorporates data suggesting an increase in aggressive behaviour amongst girls, and the still remaining statistically significant differences between girls and boys especially in the growth of aggression and in some more serious forms of aggression. Furthermore, a characteristic of aggressive student behaviours is presented taking into account six. categories: aggression and physical abuse, aggression and verbal abuse, psychological abuse, aggression and violence with objects, aggression and violence using gun, sexual abuse, and all other kinds of demoralisation and social maladjustment. A comparison of referenced findings from 2003 with those from 1997, required using not only the same research procedure (self-report questionnaire) but also taking up the very same classification of aggressive behaviours. Prevention of aggressive student behaviours can be effective if performed after correct diagnosis of such phenomenon, of its causes and only if an adequate means to diagnose will be used. An important element of the diagnosis is recognising aggression amongst students depending on the stage of their primary and secondary education. In 1997 there was no early secondary schooling yet, therefore only primary and secondary school students were verified. This very article introduces results of strengthening of different forms of aggressive behaviours in primary, lower secondary, general secondary schools, specialised secondary schools, technical secondary schools and basic vocational schools. What can be quickly noticed is a fact that all named forms of violent behaviours take place in the studied population independently of the kind of school, yet their intensity is different. These differences are provided by the received chi-squared coefficients presented in the tables. An additionally modified categorisation of aggression has been used for a more clear and efficient presentation of aggressive behaviours in schools for the future prevention. Two criteria have been taken - the strength of a deed and who it is directed at. In that way nine, instead of six, categories of aggression have been established: aggression and physical abuse, aggression against teachers, aggression against objects, psychological abuse, auto-aggression, family disobedience, verbal aggression, aggression with threatening to use a dangerous object, sexual abuse, take over, theft, being arrested by the police. For primary school the most characteristic behaviours are verbal aggression (31,1% of students admit to behave that way), physical aggression but to a lesser degree (13,7% of students), aggression against teachers (11,6%) aggression against objects (8,8%). Other forms of aggression occur less often, they are admitted by 2,6% to 5,1 % of students. In the lower secondary schools we can observe a higher figure of students using also other forms of aggression. Still the dominant form of aggression is the verbal one (38,1% of students), auto-aggression appears more strongly in form of alcohol and abuse of other psychoactive substances (19,9%), aggression against teacher has a higher level too (19%), as well as against objects (17,2%), physical abuse (12,7%). Psychological abuse, together with family disobedience occur more often than in primary schools. There is another difference in escalation of aggressive behaviours at the stage of lower secondary schools. Secondary schools, specialised secondary shools, as well as basic vocational schools, as shown in the forms of diagrams, indicate similar symptoms of aggression, the strength of such behaviours is also comparable within that group. The most common are: auto-aggression, verbal aggression, aggression against, teachers, aggression aguinst, objects, physical abuse, family disobedience, thefts, psychological abuse. Students in basic vocational schools differ in kinds and strength of aggressive behaviours. And primarily, more commonly than other students in their age, they show aggression and physical abuse. Diagnosis of aggression should not only focus on the knowledge about the offenders but also on the knowledge about the victims. This aspect has thus been discussed in this research. Twenty nine incidents of aggression have been analysed, victims of which could have been students. The aggressors could have been their colleagues, teachers, or other people. This side of a problem is not mentioned in the article. What has been under study, however, was the correlation between being an aggressor and being a victim, as well as on finding out the so-called ‘only aggressors’ and ‘only victims’. The research has confirmed the dependency between being a victim and being an aggressor. Factor analysis enabled for a differentiation of the types of ‘only aggressors’, five factors were found, and types of ‘only victims’ – seven factor found, and mixed types, ‘aggressors and victims’ - five factors. The aggression diagnosis amongst students based on the analysis of kinds of forms, their intensity and popularity within a population, is at the end of the article and it allows for stating that aggressive student behaviours are becoming a particular form of student ‘adaptation’ to the expectations of other fellow students, teachers and parents. They take more diversified forms, the number of behaviours dangerous to health and safety increases, too. Students attack teachers more often, despite the fact that teachers do try to limit their aggressive behaviours. In the student environment there is a growing number of far more serious incidents. The higher the education stage, aggressive behaviours do not decrease, the numer of aggressive students increases and the hierarchy of their order changes. The most worrying is an increase in number of students abusing alcohol and other psychoactive substances. Such behaviours are considered as forms of auto-aggression in this article. The report finishes with conclusions addressed to teachers, pedagogues, and pedagogic school supervisors for they could be included in the educational programmes and prevention methods to which schools are obliged by the adequate legal acts from the educational system and ministerial directives.